2022
DOI: 10.5812/ijem-131081
|View full text |Cite
|
Sign up to set email alerts
|

Physical Development at School Entry in Children with Congenital Hypothyroidism Diagnosed by the National Program of Newborn Screening in Iran

Abstract: Background: The newborn screening program for diagnosing and treating children with congenital hypothyroidism (CH) in Iran was established in 2004. Objectives: This study aimed to evaluate the national program’s success in maintaining the physical development and anthropometric indexes of children with CH. Methods: This historical cohort study was carried out in five provinces located in five different geographical regions of Iran. The anthropometric indexes, including weight, height, and head circumference of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Iran —Based on the success of pilot studies in three provinces, and basic support from IAEA, national NBS for CH in Iran was integrated into the national health system in 2005 and newborn coverage now exceeds 95% [ 20 , 1322 ]. To assess the quality and outcomes of the NBS program, at least three audits were completed in recent years, which showed normal growth and development at school age because of early diagnosis and treatment [ 1323 ], and good coverage but high recall and losses to follow-up. The latter program issues were addressed through the re-evaluation of cutoff levels and better surveillance of follow-up [ 1324 , 1325 ].…”
Section: Resultsmentioning
confidence: 99%
“…Iran —Based on the success of pilot studies in three provinces, and basic support from IAEA, national NBS for CH in Iran was integrated into the national health system in 2005 and newborn coverage now exceeds 95% [ 20 , 1322 ]. To assess the quality and outcomes of the NBS program, at least three audits were completed in recent years, which showed normal growth and development at school age because of early diagnosis and treatment [ 1323 ], and good coverage but high recall and losses to follow-up. The latter program issues were addressed through the re-evaluation of cutoff levels and better surveillance of follow-up [ 1324 , 1325 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that children with CH experience growth retardation. [ 29 ] However, it has been shown that early diagnosis and treatment can prevent growth retardation in patients with CH. [ 21 ] In a study conducted in 5 cities in Iran, consisting of school-age children at the age of 6 who were diagnosed with CH and healthy children, the weight was found to be similar between the 2 groups, while the height was shorter in children with CH.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] In a study conducted in 5 cities in Iran, consisting of school-age children at the age of 6 who were diagnosed with CH and healthy children, the weight was found to be similar between the 2 groups, while the height was shorter in children with CH. [ 29 ] In a study conducted in Turkey, it was found that 2.4% of school-age children between the ages of 6 to 10 had a weight-for-age below –2 SD and 5% had a length-for-age below –2 SD. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation